The benefits of adding a defibrillator to cardiac resynchronization therapy – systematic review and meta-analysis. (3rd October 2022) - Veres, B; Gharehdaghi, S; Engh, M; Schwertner, W; Kuthi, L; Merkel, E D; Masszi, R; Fehervari, P; Behon, A; Osztheimer, I; Hegyi, P; Kovacs, A; et al.
Abstract: Background: There is an long-standing debate whether cardiac resynchronisation therapy-defibrillation (CRT-D) is preferred over CRT-pacemaker (CRT-P). No randomised controlled trials have been designed to compare these treatments. However, several observational studies have been performed so far providing controversial results. Methods: PubMed, CENTRAL and Embase until October 2021 were screened for studies comparing CRT-P and CRT-D, focusing on all-cause mortality, cardiovascular mortality, sudden cardiac death, and non-cardiac death. Conference abstracts were excluded. Odds ratio with 95% confidence interval (CI) was calculated, data from the selected studies were pooled using a random effect model (Mantel-Haenszel method, where more than 5 studies with Hartung-Knapp adjustment). τ 2 was estimated by Paule-Mandel method with CI calculated by Q profile method. Statistical heterogeneity was assessed by Cochrane Q test and I 2 test. Results were summarized by Forest and drapery plots. Results: Altogether 20 observational retrospective studies (69, 124 patients) were included (CRT-P: 37, 461, CRT-D: 31, 663). CRT-D was superior to CRT-P regarding all-cause mortality in multivariate analysis (aHR: 0.79; 95% CI: 0.69–0.88; p<0.01). Based on propensity matched studies (25, 040 patients; 12, 520 CRT-P, 12, 520 CRT-D) CRT-D showed significantly better survival compared to CRT-P (HR: 0.83; 95% CI: 0.79–0.87; p<0.001). Three studies (47, 846 patients, CRT-P: 27, 344, CRT-D: 20, 502) compared cardiovascular mortality between CRT-D and CRT-P. Univariate analysis showed a significantly lower rate of cardiovascular mortality in patients implanted with a CRT-D device compared to patients with a CRT-P device (HR: 0.61; 95% CI: 0.50–0.73; p=0.002). Three studies (4, 623 patients. CRT-P: 2, 518, CRT-D: 2, 105) reported on heart failure death, where CRT-D was associated with decreased heart failure mortality compared to CRT-P (HR: 0.68; 95% CI: 0.41–0.95; p=0.008). Five studies (6, 434 patients. CRT-P: 3, 475, CRT-D: 2, 959) were analyzed for sudden cardiac death, CRT-D was superior in univariate analysis (HR: 0.33; 95% CI: 0.28–0.89; p=0.03). Three studies (48, 770 patients, CRT-P: 28, 398, CRT-D: 20, 372) reported on non-cardiac death, CRT-D showed significantly better survival than CRT-P (HR: 0.58; 95% CI: 0.55–0.60; p<0.001). Conclusion: Our meta-analysis demonstrated that patients with CRT-D had a lower risk of all-cause mortality compared to CRT-P based on those studies that used multivariate analysis and propensity score matching. Univariate analysis showed a significantly lower rate of cardiovascular heart failure mortality, sudden cardiac death, and non-cardiac death in patients implanted with a CRT-D device compared to patients with a CRT-P. However, due to the heterogeneity of the articles coming from the selection bias of patients for CRT-D/CRT-P implantation, this question requires further analysis. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The research presented here, carried out by Semmelweis University was supported by Semmelweis 250+ Excellence Scholarship (EFOP-3.6.3-VEKOP-16-2017-00009)as well as the Centre for Translational Medicine, Semmelweis University. This work was financed by the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging thematic programmes of the Semmelweis University. - I agree that this information can be anonymised and then used for statistical purposes only